Building for the Future: Evaluating Sustainable Construction Practices and Overcoming Challenges in Nigeria’s Construction Industry - Unegbu, Hyginus; Yawas, D.S.; Dan-asab, B. (Journal of Sustainable Infrastructure, 2024)
This study investigates the current state of sustainable construction practices in Nigeria, focusing on the environmental, social, and economic dimensions within the construction industry. Utilizing a quantitative research approach, data were collected through survey questionnaires distributed to construction professionals, including engineers, architects, and project managers. With a strong response rate of 95.6%, the data were analyzed using Confirmatory Factor Analysis (CFA) within the LISREL framework. The findings reveal that sustainable practices are inconsistently applied across the industry, with environmental sustainability showing the weakest emphasis. Social and economic sustainability practices also display varied levels of implementation, reflecting significant challenges in fully integrating sustainability into construction projects. The analysis points to inconsistencies and gaps, evidenced by moderate to weak associations between observed practices and their sustainability goals. To address these challenges, the study recommends that policymakers and industry leaders implement comprehensive strategies, including robust regulatory frameworks, targeted capacity-building programs, and incentives to encourage sustainable practices. Enhanced collaboration among stakeholders and increased investment in research and development are essential for fostering innovation and improving sustainability outcomes. Future research should include longitudinal studies to track the evolution of these practices over time, as well as comparative studies across different regions to identify contextual factors influencing sustainability. Additionally, qualitative research methods such as interviews and focus groups are suggested to gain deeper insights into the socio-cultural factors shaping sustainability in Nigeria's construction sector. This study contributes to a deeper understanding of the barriers and opportunities for advancing sustainable construction practices in Nigeria.